Do sex differences affect prefrontal cortex associated cognition in schizophrenia? - Roesch-Ely, Daniela; Hornberger, Eva; Weiland, Stephan; Hornstein, Christiane; Parzer, Peter; Thomas, Christine; Weisbrod, Matthias (Schizophrenia research, 2009)
Cognitive deficits in schizophrenia, especially those related to prefrontal cortex (PFC) functions, influence functional outcome. There is evidence for sex differences in cognition in schizophrenia, but the results in the literature are still controversial. - Objective - This study evaluated different modalities of working memory (WM) and executive control (EC), functions that are both associated with the PFC, between sexes in schizophrenic patients and controls. - Methods - We used a battery of neuropsychological tests for assessing auditory, spatial, and visual-matching WM and used a dual task for assessing EC. The study included 50 inpatients (25 female) partially remitted and taking atypical neuroleptics, as well as 40 controls (20 female) matched for age and education. - Results - Significant sex differences were found in the dual task; female patients detected fewer correct trials than male patients and controls did. Moreover, female patients performed significantly worse in the single visual subtest of the dual task. For the controls, no sex differences were found. Males showed higher positive symptoms than females, but no other differences in psychopathology, disease characteristics, or extrapyramidal symptoms were found between sexes. - Conclusion - The present study shows an absence of sex differences in WM in healthy subjects and in patients with schizophrenia. However, in the dual task and in the single visual subtest, female patients performed worse than males. This finding suggests that in contrast to males, nonacute female inpatients show an underlying attentional deficit that may contribute to impairment in higher-order functions such as EC.